A STUDY ON THE IMPORTANCE OF BLACK SWANS AND VAR (IITM Journal of Business Studies, 2024)
There are two general classes of likelihood spaces;  each is unmistakable, both subjectively and  quantitatively. The principal appropriation is  known as thin tail, the second is fat tail. In slight  tail disseminations, factual special cases happen  yet they don’t convey bizarrely enormous results.  In fat-tail conveyances, when critical deviations  (Black swans) happen, the results are normally  disastrous in nature. Black Swan is an occasion or  event that strays past what is regularly expected  of a circumstance and that would be very hard to  anticipate. Standard deviation is a helpful factual  estimation of hazard, if the fundamental resource  returns are circulated in a typical manner about  the mean. Be that as it may, if the benefit returns  go amiss altogether from what might be normal  in a slim tail standard deviation is regularly a  lacking and poor estimation of all out hazard  and can frequently bring about the genuine  underestimation of potential misfortunes.  VaR is genuinely exact in anticipating little  day by day misfortunes with high likelihood;  it separates totally in determining enormous  calamitous misfortunes that exist in the tail of  the dispersion – Black swan occasions. A look  at the Dow Jones Industrial Average’s greatest  one-day additions and misfortunes affirms the  presence of Black swan occasions: On every one  of two distinct days in October 2008, the Dow  flooded over 10%. On every one of eight unique  days in late 2008, the Dow gave back over 5%.  2008 was an especially unstable year, however  enormous moves can happen whenever. Right  now, hypothetical ordinariness supposition that  is observationally tried (and obviously dismissed)  utilizing time arrangement of stock returns for the  U.S. securities exchange throughout the previous  30 years. The reason for this examination is to  represent the presence of black swan occasions  and their authentic recurrence, giving specific  consideration to the timeframe 1980-2010.
Keywords: VaR; Black Swans; Thin Tail; kurtosis; fat tails